Ecological Heritage in the Family as an Effort to Support Environmental Sustainability Policies from the Perspective of Fiqh al-Bi'ah - Zulia Khoirun Nisa (Universitas Nahdlatul Ulama Blitar, 2026)
This study aims to analyze the concept of ecological inheritance within the family, the role of families in supporting environmental sustainability policies through ecological inheritance practices, and the perspective of Fiqh al-Bī'ah on ecological inheritance as an effort to promote environmental sustainability. This research integrates the concept of family ecological inheritance with the perspective of Fiqh al-Bī'ah as a normative framework to strengthen the role of families in supporting environmental sustainability policies and sustainable development. The study employs a normative legal research method using conceptual, statutory, and Islamic legal approaches. Data were collected through library research involving the Qur'an, Hadith, legislation, books, and relevant scientific journals, and were analyzed using a descriptive-qualitative method. The findings reveal that ecological inheritance is a process of transmitting environmental values, knowledge, attitudes, and conservation practices from parents to future generations through role modeling, habituation, and the development of environmentally friendly family cultures. These practices are manifested through waste management, energy and water conservation, greening activities, and responsible consumption patterns, thereby supporting the implementation of environmental sustainability policies and the achievement of the Sustainable Development Goals (SDGs). From the perspective of Fiqh al-Bī'ah, ecological inheritance represents the implementation of the principles of khalifah fil ardh (stewardship of the earth), amanah (trust), tawāzun (balance), and hifẓ al-bī'ah (environmental preservation), which aim to realize public welfare (maslahah) and prevent environmental degradation.